The effect of colchicine administration on postoperative pleural effusion following lung resection: a randomized blinded placebo-controlled feasibility pilot study. (23rd November 2017) - Agzarian, John; Bessissow, Amal; Srinathan, Sadeesh; Devereaux, Philip J; Neary, John; Decher, William; Gandy, Linda; Schneider, Laura; Finley, Christian J; Schieman, Colin; Hanna, Waël C; Shargall, Yaron
Abstract: OBJECTIVES: This substudy of the colchicine for prevention of perioperative atrial fibrillation (COP-AF) pilot trial seeks to assess the effect of colchicine administration on the volume of postoperative pleural drainage, duration of chest tube in situ and length of stay following lung resection. METHODS: Between April 2014 and April 2015, 100 patients undergoing lung resection at 2 tertiary care centres participated in a pilot blinded randomized trial comparing perioperative twice daily 0.6 mg of colchicine orally ( n  = 49) or placebo ( n  = 51) twice daily for 10 days. The primary outcome was total pleural drainage volume, which was recorded in 8-h intervals for the first 2 postoperative days per standardized protocol. RESULTS: Only 1 patient did not complete the trial. The mean volume of pleural drainage at 40-h mark postoperation was significantly less in the colchicine group (550.9 ml) compared with the placebo group (741.3 ml, P  = 0.039). Compared with the placebo group, the colchicine group showed significantly less mean pleural drainage on postoperative Day 2 (583.8 vs 763.3 ml, P  = 0.039) and beyond. There were no differences in mean time to chest tube removal (6.8 days for the colchicine group vs 5.9 days for the placebo group, P  = 0.585) and mean hospital length of stay (7.4 vs 6.9 days, P  = 0.641). CONCLUSIONS: Oral colchicine is potentially effective in diminishing the amount of pleural drainage following lung resection and can be considered in patients at high risk of large postoperative pleural effusion. A full-scale, prospective placebo-controlled randomized trial is needed to assess the clinical significance of perioperative colchicine administration following oncological lung resection.